Analisa Kegagalan Ring Piston Mesin Diesel Type YMD MAN B&W(5S35MC-C9-2) di KM. Spil Hasya - Ngatmin, Ngatmin; Oscar, Yulius; Santoso, Gunawan Budi; Juwarlan, Juwarlan; Khaeroman, Khaeroman (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The research method used was a qualitative experiment, starting with taking broken piston rings No. 2 and 3, cutting the piston rings and testing them with hardness tests and composition tests carried out at the Indonesian State Maritime Polytechnic and Undip Central Java Integrated Lab. From the results of this research, it can be concluded that the used broken ring number 3 has the highest hardness of 140.26 HB and the used ring number 2 is 131.50 HB, so it can be concluded that the piston ring that has been used and exposed to high heat causes an increase in hardness and causes it to break. The composition test results showed that the carbon content of the new ring no. 2 was the highest at 15.30% and that in the used ring no. 2 was 12.08% because the compression ring was in direct contact with the compression chamber or in contact with heat. For the used number 3 piston ring, the carbon content is 10.43 and the new one is 11.02 because it is positioned below the compression ring and is not in direct contact with heat. for the used ring no.2, the Silicon (Si) content is low, namely 2.15% compared to the new one, 2.75% because the nature of Silicium is that it is resistant to high temperatures and as a compression ring compared to ring no.3, fracture occurs because there are no Manganese or Phosphate elements. which is wear resistant, strong and elastic. The microstructure of piston ring No. 2 is broken and the new two piston rings are less dense and have rough gaps. The broken piston ring structure of No. 3 and the new one looks a bit gray and has high levels of graphite iron and carbon elements.